Evaluating level of adherence to nicotine replacement therapy and its impact on smoking cessation: a protocol for systematic review and meta-analysis - Michelle Bovill; Gillian Sandra Gould; Amanual Getnet Mersha; Parivash Eftekhari; Daniel Nigusse Tollosa (BMJ Open)
Introduction Nicotine replacement therapy (NRT) has proven effective for smoking cessation in clinical trials, however it was found less effective in population-based studies, potentially due to inconsistent or incorrect use of NRT. The aim of this paper is to describe a systematic review protocol to evaluate level of adherence to NRT; the discrepancy of adherence to NRT in clinical and population-based studies and degree of association between level of adherence and success of smoking cessation.Methods and analysis Literature search will use five databases (Medline, Scopus, Embase, CINAHL and PsycINFO). Studies will be appraised for methodological quality using National Institutes of Health Quality Assessment Tool. To reduce heterogeneity, we will analyse clinical trials and population-based studies separately; pooled analyses will be done among studies that used similar measurements. Heterogeneity of studies will be assessed by Higgins’ I2 statistical test. When studies are adequately homogeneous, results will be pooled using random-effects model with proportion and ORs with 95% CIs and p values for each outcome. We will explain sources of heterogeneity by subgroup analysis or sensitivity analysis. Funnel plots and Egger’s regression asymmetry test with p<0.05 will be used as a cut-off point to affirm presence of statistically significant publication bias. Statistical analyses will be carried out using Stata V.16 software. Only studies reporting a valid strategy to control for reverse causality will be included.Discussion This review will provide evidence to support the importance of adherence on rate of smoking cessation and level of adherence to NRT. The findings will be used to inform smoking cessation interventions, researchers and policymakers.Ethics and dissemination As a systematic literature review, this protocol does not require ethics approval. Research outcomes will be presented at relevant conferences and findings will be published in a relevant peer-reviewed journal.PROSPERO registration number CRD42020176749.